2007
DOI: 10.1016/j.modgep.2006.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Snail2, a mediator of epithelial-mesenchymal transitions, expressed in progenitor cells of the developing endocrine pancreas

Abstract: The mammalian pancreas develops by the expansion and morphogenesis of the epithelial cells of the foregut endoderm via the sequential activation of transcription factors that direct differentiation into the various pancreatic lineages. Implicit in this growth and differentiation are the temporal and spatial processes of cell migration and three-dimensional organization, which cooperate to form a properly functioning organ. In many organ systems, such as the kidney, heart, and neural crest derivatives, migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
101
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 111 publications
(104 citation statements)
references
References 27 publications
3
101
0
Order By: Relevance
“…The direct targets of Ngn3 include NeuroD1/ Beta2, Pax4, Arx, Insm1, Rfx6, Nkx2.2, Myt1, and Snail2/Slug (Huang et al, 2000;Smith et al, 2003Smith et al, , 2004Smith et al, , 2010Watada et al, 2003;Mellitzer et al, 2006;Wang et al, 2007;Rukstalis and Habener, 2007;Soyer et al, 2010) (Fig. 2B).…”
Section: Endocrine Specificationmentioning
confidence: 99%
See 2 more Smart Citations
“…The direct targets of Ngn3 include NeuroD1/ Beta2, Pax4, Arx, Insm1, Rfx6, Nkx2.2, Myt1, and Snail2/Slug (Huang et al, 2000;Smith et al, 2003Smith et al, , 2004Smith et al, , 2010Watada et al, 2003;Mellitzer et al, 2006;Wang et al, 2007;Rukstalis and Habener, 2007;Soyer et al, 2010) (Fig. 2B).…”
Section: Endocrine Specificationmentioning
confidence: 99%
“…A tantalizing suggestion comes from studies of Snail2, a well-known inducer of EMT and cell movement, which was found in scattered cells of the trunk epithelium during the secondary transition. As 80% of Ngn3 HI cells are Snail2 þ , this suggests that endocrine precursors initiate EMT very soon after commitment to endocrine fate (Rukstalis and Habener, 2007). A deeper analysis of Snail2 function in endocrine delamination and any ''epithelial backup effects'' when it is blocked will be required.…”
Section: Delamination Of Pro-endocrine Cells and Isletogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Because all pancreatic endocrine cells arise from epithelial progenitors during embryonic development, they must delaminate from the epithelium, migrate in the mesenchyme, and aggregate into clusters. There are some evidences suggesting that newly generated endocrine cells delaminate by achieving an epithelial-to-mesenchymal transition (EMT; Chiang and Melton, 2003;Rukstalis and Habener, 2007;Cole et al, 2009). EMT is a process by which an epithelial cell becomes mesenchymal and which involves profound phenotypic changes that include the loss of cell-cell adhesion, the loss of cell polarity, and the acquisition of migratory and invasive properties (Thiery et al, 2009;Acloque et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…After embryonic day (E) 14.5 in mouse embryos, it was reported that endocrine cells exhibit low E-cadherin expression and up-regulate N-cadherin, although it is unclear when this switch occurs (Hutton et al, 1993;Johansson et al, 2010). Moreover, Snail2 (previously known as Slug), a zinc finger transcription factor that promotes EMT, was shown to be expressed in the pancreas (Rukstalis and Habener, 2007). After delamination, endocrine cells migrate in the mesenchyme.…”
Section: Introductionmentioning
confidence: 99%